2010
DOI: 10.1080/03602551003749569
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of NCO-Polyol on the Properties of Low-Density Polyethylene/Water Hyacinth Fiber (Eichhornia crassiper) Composites

Abstract: Low density polyethylene (LDPE)/modified water hyacinth fiber (WHF) composites have been prepared by melt blending. All the composites were characterized by tensile test, differential scanning calorimetry (DSC), water absorption behaviour, thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). The results indicated that LDPE/WHF composites with NCO-polyol as a coupling agent show higher values of tensile strength, Young's modulus and water absorption resistance but lower elongation at break t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…They concluded that the increasing addition of wood flour caused a small but progressive improvement of the decomposition temperature of the composites, whereas the glass transition temperature remained practically unchanged, and a gradual decrease in T 1 H values was observed with increasing wood content, indicating that the composites became less rigid. Nourbakhsh and Ashori [16] investigated four levels of fiber loading (10,20,30, and 40 wt%) on the mechanical properties of poplar=PP composites. They found that the fiber loading of 30 and 40 wt% at 190 C provided adequate reinforcement to increase the tensile and flexural strength of the PP power, the modulus increased, and the elongation and impact properties of the composites decreased with increasing the fiber content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the increasing addition of wood flour caused a small but progressive improvement of the decomposition temperature of the composites, whereas the glass transition temperature remained practically unchanged, and a gradual decrease in T 1 H values was observed with increasing wood content, indicating that the composites became less rigid. Nourbakhsh and Ashori [16] investigated four levels of fiber loading (10,20,30, and 40 wt%) on the mechanical properties of poplar=PP composites. They found that the fiber loading of 30 and 40 wt% at 190 C provided adequate reinforcement to increase the tensile and flexural strength of the PP power, the modulus increased, and the elongation and impact properties of the composites decreased with increasing the fiber content.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of natural materials have been used in WPCs [18][19][20][21]. Among the various natural materials, wood fibers have attracted considerable attention in the fields of both fundamental research and applications due to their ease of handling and widespread availability [22].…”
Section: Introductionmentioning
confidence: 99%
“…The crystallinity of the composites was determined by using the relationship % Crystallinity = Δ H f Δ Hf × 100 % where Δ H f and Δ H ° f are enthalpy of fusion of the composite and enthalpy of fusion of LDPE, respectively. The value for Δ H ° f (LDPE) is 293.6 J/g .…”
Section: Methodsmentioning
confidence: 97%
“…where DH f and DH8 f are enthalpy of fusion of the composite and enthalpy of fusion of LDPE, respectively. The value for DH8 f (LDPE) is 293.6 J/g [1,2].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…Blending polymers with fillers is a common industrial practice for various types of polymer, which leads to properties that are superior to those of the component polymers alone. The addition of inorganic fillers to polymers has received considerable attention lately [1][2][3], for economic reasons as well as for the favorable modification of mechanical, electrical, and thermal properties [4].…”
Section: Introductionmentioning
confidence: 99%